Optimisation of the resource efficiency in an industrial evaporation system. (August 2017) - Pitarch, J.L.; Palacín, C.G.; De Prada, C.; Voglauer, B.; Seyfriedsberger, G.
Abstract : Highlights: Resource-efficiency indicators are computed to assess decisions in real time. Evaluating actual process efficiency requires comparing with a best-case situation. Data reconciliation is used to obtain a reliable set of values for process variables. RTO routines for optimal operation and scheduling of the cleaning tasks are given. Modern optimisation software is key to obtain accurate solutions in real time. Abstract: This work deals with the problem of resource efficiency monitoring in a multiple-effect evaporation process. The approach considers first a grey-box nonlinear stationary model of the process and data-reconciliation methods to compute efficiency indicators and to update such model if necessary. The updated model is used in a real-time optimisation layer to compute operation points of the process. Then, some patterns for optimal operation have been identified and implemented by a self-optimising controller to drive the process. In a second step, the fouling, which reduce the heat-transfer efficiency in heat exchangers, is also considered as a function of time and control decisions, in order to optimally drive the process considering the long-term effect. This fouling behaviour forces periodic stops for cleaning, which will be also object of optimisation. Finally, the overall problem is formulated as a real-time optimisation to search for the optimal decisions during a whole operation cycle.